INNOVATIVE APPROACHES TO INCREASE THE EFFICIENCY AND SUSTAINABLE DEVELOPMENT OF FEED PRODUCTION (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2026)
The article examines the importance of organic feed production for livestock in the context of growing demand for environmentally friendly products. It emphasizes that consumers prefer products without synthetic additives, which makes organic feed important for livestock. The authors note that natural feed components reduce the risk of diseases, increase animal productivity and reduce dependence on antibiotics.The article also analyzes international experience in the creation of bioengineering technologies for the production of probiotics and enzymes that improve livestock health without the use of synthetic substances. Research focuses on the biological aspects of organic feeds, their ability to improve digestion, increase animal immunity and reduce the negative effects of pathogenic microorganisms. Particular attention is paid to the classification of organic feeds and their functionality.The article highlights the prospects for the development of organic animal husbandry in Ukraine, where the production of organic feed is growing thanks to the use of local resources and traditional fermentation technologies. It calls for the introduction of new technologies and innovative solutions to improve the quality of feed and animal health, contributing to the general increase in standards of organic production.
Keywords: organic fodder; ecological products; probiotics; enzymes; animal husbandry; livestock health